PENDAMPINGAN ADOPSI TEKNOLOGI PEMBAYARAN DIGITAL: MENGUATKAN UMKM MELALUI IMPLEMENTASI QRIS DI KOTA PEKANBARU - Darni, Darni; Illosa, Abdiana; Hayani, Nurrahmi; Sumayyah, Yety; Nazera, Wilda (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
This community service project aims to accelerate the adoption of digital payment technology among Micro, Small, and Medium Enterprises (MSMEs) in Pekanbaru City through the implementation of QRIS (Quick Response Code Indonesian Standard). The initiative was driven by the low level of digital literacy, limited transaction efficiency, and the growing need for secure and transparent payment systems. The project employed a service learning approach, engaging university students in five main phases: investigation, planning, implementation, evaluation, and reflection. A total of 86 students from three classes were involved in assisting selected MSMEs through socialization, technical training, and direct application of QRIS in their daily transactions. The results indicate a significant improvement in both the understanding and usage of QRIS among MSME partners, although challenges such as limited internet access and concerns over transaction fees were still encountered. Evaluation was conducted through surveys, interviews, and field observations, while student reflections revealed that the activity effectively enhanced their academic and social competencies. This project demonstrates that collaborative engagement between universities and local communities can serve as an effective strategy to support the sustainable digital transformation of MSMEs.